Electrode Dependence of Tunneling Electroresistance and Switching Stability in Organic Ferroelectric P(VDF‐TrFE)‐Based Tunnel Junctions. (27th November 2017) - Majumdar, Sayani; Chen, Binbin; Qin, Qi Hang; Majumdar, Himadri S.; van Dijken, Sebastiaan
Abstract: Ferroelectric tunnel junctions (FTJs) are promising candidates for nonvolatile memories and memristor‐based computing circuits. Thus far, most research has focused on FTJs with a perovskite oxide ferroelectric tunnel barrier. As the need for high‐temperature epitaxial film growth challenges the technological application of such inorganic junctions, more easily processable organic ferroelectrics can serve as alternative if large tunneling electroresistance (TER) and good switching durability would persist. This study reports on the performance of FTJs with a spin‐coated ferroelectric P(VDF‐TrFE) copolymer tunnel barrier. The use of three different bottom electrodes, indium tin oxide (ITO), La0.67 Sr0.33 MnO3, (LSMO), and Nb‐doped SrTiO3 (STO) are compared and it is shown that the polarity and magnitude of the TER effect depend on their conductivity. The largest TER of up to 10 7 % at room temperature is measured on FTJs with a semiconducting Nb‐doped STO electrode. This large switching effect is attributed to the formation of an extra barrier over the space charge region in the substrate. The organic FTJs exhibit good resistance retention and switching endurance up to 380 K, which is just below the ferroelectric Curie temperature of the P(VDF‐TrFE) barrier. Abstract : A room‐temperature, giant resistive switching effect of 10 7 % is demonstrated in organic ferroelectric tunnel junctions with an ultrathin P(VDF‐TrFE) copolymer barrier. The switching magnitude and polarity strongly depend on the bottom electrode, with semiconducting Nb‐doped SrTiO3 providing superior OFF/ON resistance ratios. P(VDF‐TrFE)'s ease of fabrication, stability, and compatibility with almost any electrode material make it a promising candidate for nonvolatile memories.